2022
DOI: 10.1515/sjpain-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure for pain and comorbid PTSD: a single-case experimental study of a treatment supplement to multiprofessional pain rehabilitation

Abstract: Objectives It is unclear how to address PTSD in the context of chronic pain management. Here we examine the potential benefits of an addition of prolonged exposure (PE) therapy for PTSD for adults attending multidisciplinary CBT for chronic pain. Methods Four adults seeking treatment for chronic pain from a specialized pain rehabilitation service were offered PE for PTSD using a replicated, randomized, single-case experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The treatment for PTSD in chronic pain has been evaluated in a single case experimental design study (n=4) but has not been further examined. In the single case study, each of the four cases showed clinically relevant improvements in symptoms of PTSD and beliefs related to trauma 71. These new approaches that include comorbid problems are not “one size fits all” packages of treatment components delivered as a whole for everyone meeting entry criteria for treatment.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The treatment for PTSD in chronic pain has been evaluated in a single case experimental design study (n=4) but has not been further examined. In the single case study, each of the four cases showed clinically relevant improvements in symptoms of PTSD and beliefs related to trauma 71. These new approaches that include comorbid problems are not “one size fits all” packages of treatment components delivered as a whole for everyone meeting entry criteria for treatment.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…For the latter, the focus is on behavioral activation for depression in the context of chronic pain, 70 a combination of ACT plus mindfulness based prevention of relapse in problematic opioid use, 49 or the addition of prolonged exposure to traumatic reminders for people with chronic pain and post-traumatic stress disorder (PTSD). 71 The clinical trial for the study focused on depression is registered and recruitment has started (ClinicalTrials.gov, NCT04140838). For the treatment focused on problematic opioid use in chronic pain, an initial feasibility and preliminary efficacy study (n=35) has been completed and compares the integrated treatment with treatment as usual in military veterans.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 , 29 There is a growing body of research showing the benefits of simultaneously treating post-traumatic stress and chronic pain in particular. 30 - 35 Given synergies in cognitive-behavioural treatments for pain and mental health, research is needed to better understand how best to integrate treatments for both of these difficulties to further promote inclusion. 29 …”
Section: Discussionmentioning
confidence: 99%